2007
DOI: 10.1002/pbc.21377
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of children with aplastic anemia treated with immunosuppressive therapy

Abstract: Background Immunosuppressive therapy (IST) is the alternative treatment in children with aplastic anemia (AA) who do not have an HLA‐matched sibling. The aim of this study is to evaluate the outcome of children with AA treated with IST. Methods We retrospectively reviewed the hospital records of children with AA from 1984 to 2004, treated at our institution with antithymocyte globulin (ATG), cyclosporine (CS), and short course of prednisone. Result Forty‐two patients were treated with IST (24 boys, 18 girls); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 30 publications
5
41
1
Order By: Relevance
“…The present study of 37 SAA patients treated with IST showed CR and PR rates of greater than 75%, with a robust function with regard to both tacrolimus-and CsA-based therapies. Compared to the previously reported clonal transformation rates of approximately 10% for CsA-based IST [20,[22][23][24][25], no clonal transformation to PNH or MDS/AML was observed in either of our groups. A recent study on pediatric SAA reported that tacrolimus could be used as an alternative to cyclosporine in the maintenance phase of IST, with 88% PR; in this eight-case study, one case failed to response to IST-based therapy and subsequently underwent successful unrelated cord blood HSCT, and one patient showed PNH transformation, as detected using flow cytometry [28].…”
Section: Discussioncontrasting
confidence: 81%
“…The present study of 37 SAA patients treated with IST showed CR and PR rates of greater than 75%, with a robust function with regard to both tacrolimus-and CsA-based therapies. Compared to the previously reported clonal transformation rates of approximately 10% for CsA-based IST [20,[22][23][24][25], no clonal transformation to PNH or MDS/AML was observed in either of our groups. A recent study on pediatric SAA reported that tacrolimus could be used as an alternative to cyclosporine in the maintenance phase of IST, with 88% PR; in this eight-case study, one case failed to response to IST-based therapy and subsequently underwent successful unrelated cord blood HSCT, and one patient showed PNH transformation, as detected using flow cytometry [28].…”
Section: Discussioncontrasting
confidence: 81%
“…They evaluated the efficacy of immunosuppressive therapy (IST) with antithymocyte globulin (ATG) and cyclosporine (CSA) on 33 pediatric patients with acquired aplastic anemia in the Indian setting. Their results indicate that in India, with appropriate supportive care, pediatric aplastic anemia patients treated with IST can achieve response rates similar to North America and Europe, where the response rate is as high as 81% [2]. In addition, they confirm the experience of other authors, that ATG and CSA alone are the backbone of IST in treating childhood aplastic anemia, and that administration of G-CSF reduced infectious complications, but had no impact on survival or outcome [3].…”
Section: Immunotherapy For Childhood Aplastic Anemia In Indiasupporting
confidence: 57%
“…The data yields other interesting trends: compared to the 42 pediatric patients treated with IST in Toronto by Pongtanakul, et al [2], although response rates were similar (88 vs 81%), there was a significant decrease in the percentage of patients with complete response (CR) (24% vs 62%) with an increase in partial response (PR) (64% vs 19%). This predominance of partial responders was seen also in another Indian series reported by Chandra, et al [5], who raised the question of effective cyclosporine administration, given the expense and uncertain quality in the open market.…”
Section: Vikramjit S Kanwarmentioning
confidence: 56%
See 1 more Smart Citation
“…39 Response rates to IST in children are favorable, with survival ranging from 68% in one institution to 80% in another retrospective study at 10 years, with 89% survival if the analysis is confined to responders to IST. [40][41][42] There are data demonstrating the risk for malignant evolution over time with IST therapy, with rates of MDS/acute myelogenous leukemia ranging from 8 to 25%. 9,43 Modifications to the conventional IST regimen, including addition of danazol, mycophenolate mofetil, sirolimus or hematopoietic growth factors, have not significantly improved response or decreased relapse rates.…”
Section: Immunosuppressive Therapymentioning
confidence: 99%